Sequential Use of Second-Generation Tyrosine Kinase Inhibitor Treatment and Intensive Chemotherapy Induced Long-Term Complete Molecular Response in Imatinib-Resistant CML Patient Presenting as a Myeloid Blast Crisis. (17th December 2017) - Tsuji, Masaaki; Uchiyama, Tatsuki; Mizumoto, Chisaki; Takeoka, Tomoharu; Tomo, Kenjiro; Ohno, Tatsuharu
Abstract : Myeloid blast crisis of chronic myeloid leukemia (CML-MBC) is rarely seen at presentation and has a poor prognosis. There is no standard therapy for CML-MBC. It is often difficult to distinguish CML-MBC from acute myeloid leukemia expressing the Philadelphia chromosome (Ph+ AML). We present a case in which CML-MBC was seen at the initial presentation in a 75-year-old male. He was treated with conventional AML-directed chemotherapy followed by imatinib mesylate monotherapy, which failed to induce response. However, he achieved long-term complete molecular response after combination therapy involving dasatinib, a second-generation tyrosine kinase inhibitor, and conventional chemotherapy.